LEARNING USING FLIPBOOK-BASED E-MODULES TO IMPROVE LEARNING OUTCOMES OF UNDERSTANDING THE FUNCTION OF MACHINE PARTS FOR STUDENTS OF THE MACHINING ENGINEERING EXPERTISE PROGRAM CLASS XI SMK NEGERI 1 KARANGAWEN - Risma Faqih Rachman; Muhammad Khumaedi (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study aims to analyze the effectiveness of the use of flipbook-based e-modules in improving student learning outcomes in the material of understanding the function of fresh machine parts in the Machining Engineering Expertise Program of SMK Negeri 1 Karangawen. The study employed a nonequivalent control group design and a quantitative, quasi-experimental methodology. Twenty-five students from the experimental class and twenty-five from the control class made up the research sample. Observation, documentation, expert validation, and learning outcome tests in the form of pretests and posttests are utilized to acquire data. Data were analyzed using descriptive analysis, normality test, homogeneity test, independent sample t-test, and N-Gain analysis. The experimental class's average posttest score was 92.88, which was greater than the control group's mean of 73.12. Furthermore, the N-Gain analysis revealed that the experimental class had an average increase in learning outcomes of 85.64% in the high category, compared to 45.14% in the medium category for the control class. These findings suggest that using flipbook-based e-modules can enhance students' comprehension and learning outcomes about the functional content of the milling machine's components.